2022
DOI: 10.1097/ta.0000000000003801
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitative practices and the use of low-titer group O whole blood in pediatric trauma

Abstract: Increasing rates of penetrating trauma in the United States makes rapid identification of hemorrhagic shock, coagulopathy, and early initiation of balanced resuscitation in injured children of critical importance. Hemorrhagic shock begins early after injury and can be challenging to identify in children, as hypotension is a late sign that a child is on the verge of circulatory collapse and should be aggressively resuscitated. Recent data support shifting away from crystalloid and toward early resuscitation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
1
3
0
Order By: Relevance
“…Our findings support the idea that whole blood's primary benefit lies in its logistical simplicity and improvement in efficiency and resource utilization outcomes. In keeping with most prior studies in adults and children, we did not see an association between whole blood and mortality 8,37 . As of this writing, only one single-center study has demonstrated improved survival with whole blood resuscitation in children 38 …”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our findings support the idea that whole blood's primary benefit lies in its logistical simplicity and improvement in efficiency and resource utilization outcomes. In keeping with most prior studies in adults and children, we did not see an association between whole blood and mortality 8,37 . As of this writing, only one single-center study has demonstrated improved survival with whole blood resuscitation in children 38 …”
Section: Discussionsupporting
confidence: 83%
“…In keeping with most prior studies in adults and children, we did not see an association between whole blood and mortality. 8,37 As of this writing, only one single-center study has demonstrated improved survival with whole blood resuscitation in children. 38 This study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations